2013
DOI: 10.1128/genomea.00629-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis ofAcheta domesticusDensovirus Isolates from Different Outbreaks in Europe, North America, and Japan

Abstract: The first densovirus from a cricket, Acheta domesticus densovirus (AdDNV) (Parvoviridae), was isolated in Europe in 1977 and has been studied previously. We compared seven additional AdDNV genomes isolated from 4 other European outbreaks, 2 major North American outbreaks, and a Japanese outbreak. Phylogenetic analysis suggested that the 2009 Japanese and North American outbreaks were not related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Phylograms based on genome sequences and deduced proteins confirmed that AdDNV and PcDNV were closely related species within Ambidensovirus (Supplementary Fig. S1 and Supplementary Text S1 ) 43 , 49 57 .
Figure 2 Genome coverage and annotations of AdDNV and PcDNV.
…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Phylograms based on genome sequences and deduced proteins confirmed that AdDNV and PcDNV were closely related species within Ambidensovirus (Supplementary Fig. S1 and Supplementary Text S1 ) 43 , 49 57 .
Figure 2 Genome coverage and annotations of AdDNV and PcDNV.
…”
Section: Resultsmentioning
confidence: 79%
“…Two transcriptomes obtained from the 1000 Insect Transcriptome Evolution project (1KITE, www.1kite.org ) 42 were analyzed in this study: house cricket ( Acheta domesticus (Linnaeus), Orthoptera, Gryllidae) and citrus mealybug ( Planococcus citri (Risso), Hemiptera, Pseudococcidae). Previous studies suggest these insects often carry closely related viruses - Acheta domesticus densovirus (AdDNV) and Planococcus citri densovirus (PcDNV), respectively 43 , 44 . Densoviruses (family Parvoviridae ) are widely distributed among arthropods 19 , 45 with linear single-stranded DNA genomes of approximately 5,000-nucleotides, including two major gene cassettes encoding viral nonstructural (NS or Rep) and structural proteins (VP or CP) 43 , 45 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the present time, the reported viruses consist of insect viruses but no human foodborne viruses have been identified in this specimen [81]. Today, the main virus affecting A. domesticus industry is Acheta domesticus densovirus, which is able to decimate commercial mass rearings in just a few days, leading to a fall in production and even extinction of local cricket populations [44,88,[108][109][110]. This virus was first isolated from diseased A. domesticus from a Swiss commercial mass rearing facility in 1977 [111].…”
Section: Acheta Domesticusmentioning
confidence: 94%
“…The cricket industry has been devastated worldwide recently by the Acheta domesticus densovirus (AdDNV) ( 1 4 ). We also observed several, thus far unknown, viruses such as volvoviruses, which have circular, single-stranded DNA (ssDNA) genomes ( 5 ), and a new densovirus (parvovirus).…”
Section: Genome Announcementmentioning
confidence: 99%